Expanding the Plant GSTome Through Directed Evolution: DNA Shuffling for the Generation of New Synthetic Enzymes With Engineered Catalytic and Binding Properties - Chronopoulou, Evangelia G.; Papageorgiou, Anastassios C.; Ataya, Farid; Nianiou-Obeidat, Irini; Madesis, Panagiotis; Labrou, Nikolaos E. (Frontiers in Plant Science, 2018)
Glutathione transferases (GSTs, EC. 2.5.1.18) are inducible multifunctional enzymes that are essential in the detoxification and degradation of toxic compounds. GSTs have considerable biotechnological potential. In the present work, a new method for the generation of synthetic GSTs was developed. Abiotic stress treatment of Phaseolus vulgaris and Glycine max plants led to the induction of total GST activity and allowed the creation of a GST-enriched cDNA library using degenerated GST-specific primers and reverse transcription-PCR. This library was further diversified by employing directed evolution through DNA shuffling. Activity screening of the evolved library led to the identification of a novel tau class GST enzyme (PvGmGSTUG). The enzyme was purified by affinity chromatography, characterized by kinetic analysis, and its structure was determined by X-ray crystallography. Interestingly, PvGmGSTUG displayed enhanced glutathione hydroperoxidase activity, which was significantly greater than that reported so far for natural tau class GSTs. In addition, the enzyme displayed unusual cooperative kinetics towards 1-chloro-2,4-dinitrochlorobenzene but not towards glutathione. The present work provides an easy approach for the simultaneous shuffling of GST genes from different plants, thus allowing the directed evolution of plants GSTome. This may permit the generation of new synthetic enzymes with interesting properties that are valuable in biotechnology.